1997
DOI: 10.1074/jbc.272.32.19814
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between the Platelet-derived Growth Factor and the Insulin Signaling Pathways in 3T3-L1 Adipocytes

Abstract: Phosphatidylinositol (PI) 3-kinase is activated by various growth factors such as PDGF (platelet-derived growth factor) and insulin. The aim of the present study was to determine whether PDGF could modulate insulin activation of PI 3-kinase in 3T3-L1 adipocytes. When cells were preincubated for 5-15 min with PDGF, PI 3-kinase activity associated to insulin receptor substrate 1 (IRS 1) in response to insulin was decreased, due to reduced association of the PI 3-kinase p85 subunit with IRS 1. In addition, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 34 publications
3
41
0
1
Order By: Relevance
“…Preincubation of MCF-7 cells with IGFBP-3 was found to inhibit IGF-IR activation independently of IGFBP-3's ability to bind IGFs (13) and possibly involving conformational changes (14). IGFBP-3 could also alter IRS-1 phosphorylation, as shown in other systems where serine/threonine phosphorylation inhibits tyrosine phosphorylation in response to insulin, hence down-regulating subsequent insulin signaling (21,22). However, this appeared unlikely, since serine/threonine phosphorylation of IRS-1 results in an increase of its molecular mass, which is visible in SDS-PAGE, but which did not occur in our experiments.…”
Section: Discussionmentioning
confidence: 82%
“…Preincubation of MCF-7 cells with IGFBP-3 was found to inhibit IGF-IR activation independently of IGFBP-3's ability to bind IGFs (13) and possibly involving conformational changes (14). IGFBP-3 could also alter IRS-1 phosphorylation, as shown in other systems where serine/threonine phosphorylation inhibits tyrosine phosphorylation in response to insulin, hence down-regulating subsequent insulin signaling (21,22). However, this appeared unlikely, since serine/threonine phosphorylation of IRS-1 results in an increase of its molecular mass, which is visible in SDS-PAGE, but which did not occur in our experiments.…”
Section: Discussionmentioning
confidence: 82%
“…This feature is also shared by several growth factors that inhibit insulin signaling through serine phosphorylation of IRS-1. Platelet-derived growth factor inhibits insulin-induced tyrosine phosphorylation of IRS-1 in 3T3-L1 adipocytes, and PI3K inhibitors abrogate this effect (42)(43)(44). In the same cells EGF reduces tyrosine phosphorylation of IRS-1 via an MEK-ERK1/ 2-dependent pathway (25).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed that insulin stimulation resulted in a slow rise and sustained PI 3-kinase activity in 3T3-L1 cells, whereas PDGF resulted in rapid and transient PI 3-kinase activity (Ricort et al 1997). Visualization of PtdIns(3,4,5)P 3 at the leading edge of motile cells can be accomplished with either a GFP-PH domain (Rickert et al 2000) or with the RC6F8 IgM described herein (H. Bourne, personal communication).…”
Section: Discussionmentioning
confidence: 99%